Inorganic–Organic Hybrid Electrolytes Based on Al-Doped Li7La3Zr2O12 and Ionic Liquids - Akiko Tsurumaki; Rossella Rettaroli; Lucia Mazzapioda; Maria Assunta Navarra (Applied Sciences, 2022)
Organic–inorganic hybrid electrolytes based on Al-doped Li7La3Zr2O12 (LLZO) and two different ionic liquids (ILs), namely N-ethoxyethyl-N-methylpiperidinium bis(fluorosulfonyl)imide (FSI IL) and N-ethoxyethyl-N-methylpiperidinium difluoro(oxalato)borate (DFOB IL), were prepared with the aim of improvement of inherent flexibilities of inorganic solid electrolytes. The composites were evaluated in terms of thermal, spectroscopical, and electrochemical properties. In the impedance spectra of LLZO composites with 15 wt% ILs, a semi-circle due to grain boundary resistances was not observed. With the sample merely pressed with 1 ton, without any high-temperature sintering process, the ionic conductivity of 10−3 S cm−1 was achieved at room temperature. Employing a ternary composite of LLZO, FSI IL, and LiFSI as an electrolyte, all-solid-state lithium metal batteries having LiFePO4 as a cathode were assembled. The cell exhibited a capacity above 100 mAh g−1 throughout the course of charge–discharge cycle at C/20. This confirms that FSI IL is an effective additive for inorganic solid electrolytes, which can guarantee the ion conduction.